Face stability assessment of a longitudinally inclined tunnel considering pore water pressure - Chen, Guang‐Hui; Zou, Jin‐Feng; Guo, Yuan‐Cheng; Tan, Zi‐An; Dan, Shu (International journal for numerical and analytical methods in geomechanics, 2024)
The face stability analysis of a longitudinally inclined shield tunnel using an analytical approach in water‐rich areas is still a research gap. To solve this face stability problem, a numerical simulation based on the FLAC3D is first conducted to calculate the seepage field behind the inclined tunnel face. An improved rotational failure mechanism is developed to make it possible to investigate the face stability of inclined tunnels using analytical approaches. In the framework of the kinematic approach of limit analysis, the limit support pressures and corresponding failure surfaces of the inclined tunnel face are determined to analyze the face stability issue. The interpolation tool (griddata) in MATLAB is adopted to involve the obtained numerical values of pore water pressures into the analysis of the stability issue. The analytical solutions obtained from the proposed method are validated by comparisons with existing results from published literatures and numerical results. For a quick estimation of the inclined tunnel face stability in water‐rich areas, a series of design charts are then presented for various soil strength parameters, water tables, and inclined angles. Finally, an application of the proposed method to a practical tunneling case is provided, which further illustrates the effectiveness of the proposed method.